Studi Eksperimental Pemasangan Oil Catch Tank (OCT) Pada Mesin 3SZ- VE Terhadap Emisi Gas Buang Dan Prestasi Mesin Yang Dihasilkan - Yudhanta, Ricko; W. Praja, Sumantri; Schouten, Femmy; Widyanto, Utut; Boedi, Hari (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2025)
The use of an Oil Catch Tank (OCT) is intended to optimize the clean air entering the intake manifold and reduce vehicle exhaust emissions. The main function of the OCT is to prevent oil particles or oil vapors from re-entering the intake system. Blow-by gases from the crankcase first enter the OCT tube, where they are trapped by a filter medium (steel wool), allowing only clean air to reach the combustion chamber. From the experimental results, across all OCT filter variations, the lowest CO levels were recorded at 1000 rpm, while the highest CO occurred at 3500 rpm. The highest CO level of 20.97% vol was found under standard vehicle conditions at 4500 rpm. The lowest HC value of 93.57 ppm vol was obtained using a 0.5-micron OCT filter at 5000 rpm. The highest torque and power values of 143 Nm and 108.65 HP, respectively, were achieved when using a 1-micron filter OCT at 6000 rpm. This study confirms that OCT installation can significantly reduce exhaust emissions and improve engine performance. These findings contribute to addressing global environmental concerns, particularly air pollution and climate change caused by the transportation sector. Furthermore, the results support the broader adoption of environmentally friendly automotive technologies, especially in enhancing combustion efficiency and emission control in internal combustion engine vehicles.